Development of physical activity games in improving the physical motor ability of children aged 10-11 years at the elementary school level - Sabaruddin Yunis Bangun; Miftahul Irfanda Harahap; R. Syaifullah D. Sihombing (Jurnal Keolahragaan, 2023)
The purpose of this study was to develop physical activity games to improve the physical motor ability of children aged 10-11 years at the elementary school level. Using research and development/RD methods. Data collection techniques through questionnaires/questions given to experts and students, the data analysis technique used in this study is quantitative percentages. Validated by material experts, game experts, and language experts. The percentage of product design validation by experts is 80%, based on the information in the expert validation assessment table, the average value is in the range of 80%-100% valid meaning is used. The percentage of small group trials by target or object is 73%, based on the information in the table of evaluation criteria for the implementation of trial activities, the average value is in the range of 65%-82%, with good classification means used. The percentage of product design validation by experts in small group trials is 90% based on the information in the expert validation assessment table, so the average value is in the range of 80%-100% valid information means used. The percentage of large group trials by target or object is 90%, based on the information in the table of criteria for assessing the implementation of trial activities, the average value is in the range of 83%-100% very good classification meaning used. After going through the repeated validation stages and comparing small group trials and large group trials, it can be concluded that the development of physical activity games in improving the physical motor skills of children aged 10-11 years at the elementary school level is said to be very good and valid meaning is used